The Influence of Booklets and Videos on the Ability to Practice Breast Self Examination in Students of High School 4 Gorontalo - Nancy Olii; Nurnaningsih Ali Abdul (Indian Journal of Forensic Medicine & Toxicology, 2021)
Individual awareness in taking actions properly BSE is influenced by the individual understanding ofbreast cancer, so health promotion Efforts are Necessary. Videos and booklets are some alternative healthpromotion media. The research objective was to determine the effect of booklets and videos on the abilityto practice breast self-examination on students at High school 4 Gorontalo . The research used the PreExperiment method with a one-group pretest-posttest design, Carried out in August-October 2019 at Highschool 4 Gorontalo . The research sample was 60 female students from a population of 119 students usingthe purposive sampling technique. Statistical test using Paired t-test. The results of the analysis of thedifferent test on the ability of Breast Self Examination (BSE) before and after reading the booklet showedthat there was a difference in BSE ability with p-value = 0.001, while before and after watching the videoshowed that there was a difference in BSE ability with p = 0.001 (p <0.05). This study concluded that therewas an increase in the students’ BSE practice skills after reading booklets and watching BSE videos atHigh School 4 Gorontalo. It is hoped that students can increase their knowledge and apply BSE so that theincidence of breast cancer or breast disorders can be prevented and detected early.